Internet: Importance and Usage for Library and Information Professionals - Singh, Neena (DESIDOC Journal of Library & Information Technology, 2003)
The paper focuses on the impact of lnternet on various library processes, services and products. It also emphasises the challenging role of librarians and information professionals in the present lnternet era. Today the lnternet has revolutionised the traditional library activities viz document acquisition, teclinical processing, circubtion, reference service, resource sharing, document delivery, etc. The paper also emphasises the crucial role of librarians and information professionals in designing and maintaining libraries' web page/website leading to increase in library efficiency. http://dx.doi.org/10.14429/dbit.21.3.3542